2017
DOI: 10.1111/jomf.12418
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure Stress, Social Support, and Depressive Symptoms Among Cisgender Bisexual Youth

Abstract: Bisexual youth are at elevated risk for depression compared to lesbians and gay men. Research on bisexual stigma suggests these youth are uniquely vulnerable to stress related to sexual identity disclosure. Depression associated with this stress may be buffered by social support from parents and friends. We examined the differential influence of social support from parents and friends (Child and Adolescent Social Support Scale) on the relation between disclosure stress (LGBTQ Coming Out Stress Scale) and depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 57 publications
1
68
0
1
Order By: Relevance
“…Although we could identify few qualitative or theoretical studies examining mental health among bisexual youth specifically, it may be that bisexual youth face additional challenges in developing and disclosing a sexual identity label that is not only stigmatized but also highly invisible and poorly understood by many potential support people (Flanders et al, 2015;Ross et al, 2010). In their quantitative study of nearly 400 bisexual youth, Pollitt, Muraco, Grossman, and Russell (2017) found that depressive symptoms were positively correlated with disclosure stress and negatively correlated with support from close friends and from family; in multivariate analyses, support from parents buffered the relationship between family disclosure stress and symptoms of depression. However, the determinants of bisexual mental health we have discussed (bisexual-specific discrimination; bisexuality invisibility; lack of bisexual affirmative support) may be modified by age, in that their effects may become stronger as bisexual people age.…”
Section: Important Intersectionsmentioning
confidence: 99%
“…Although we could identify few qualitative or theoretical studies examining mental health among bisexual youth specifically, it may be that bisexual youth face additional challenges in developing and disclosing a sexual identity label that is not only stigmatized but also highly invisible and poorly understood by many potential support people (Flanders et al, 2015;Ross et al, 2010). In their quantitative study of nearly 400 bisexual youth, Pollitt, Muraco, Grossman, and Russell (2017) found that depressive symptoms were positively correlated with disclosure stress and negatively correlated with support from close friends and from family; in multivariate analyses, support from parents buffered the relationship between family disclosure stress and symptoms of depression. However, the determinants of bisexual mental health we have discussed (bisexual-specific discrimination; bisexuality invisibility; lack of bisexual affirmative support) may be modified by age, in that their effects may become stronger as bisexual people age.…”
Section: Important Intersectionsmentioning
confidence: 99%
“…Though we know support from family members during disclosure is particularly important for bisexual men (Shilo & Savaya, 2011; Shilo & Savaya, 2012), we did not test whether these community/family members actually supported the individuals’ bisexual identities. Research shows that support from parents predicts lower depressive symptoms among bisexual men, especially when these men experience stress when disclosing to family members (Pollitt et al, 2017). Related to our finding of null results for disclosure to family for most sexual health outcomes, bisexual men who are out to their family members may be less likely to self-disclose that they have an STI because they may not want to jeopardize these family relationships (D’Augelli, Hershberger, & Pilkington, 1998; Dodge, Jeffries, & Sandfort, 2008; Friedman, Marshal, Stall, Cheong, & Wright, 2008; McGarrity & Huebner, 2014; Scherrer et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Some research suggests that bisexual individuals have worse health outcomes compared to gay and lesbian individuals (see Ross et al, 2017 for a systematic review and meta-analysis), which is oftentimes a result of heterosexism (i.e., prejudice against sexual minority individuals based on the assertion that being ‘heterosexual’ is ‘normal’) and less support from friends and family members (Crawford, Allison, Zamboni, & Soto, 2002; Dodge et al, 2007; Jorm, Korten, Rodgers, Jacomb, & Christensen, 2002; Pollitt, Muraco, Grossman, & Russell, 2017; Roberts, Horne, & Hoyt, 2015). The relationship between heterosexism and health is in part enhanced for bisexual people because heterosexual and gay/lesbian communities can stigmatize bisexuality as an invalid identity; bisexual individuals are sometimes regarded as possessing an invisible identity (Roberts et al, 2015).…”
mentioning
confidence: 99%
“…In the study by Feinstein, Wadsworth, Davila, and Goldfried (2014), family support served as a protective factor against the development of internalized homophobia in lesbians and gay men. In bisexual men, parental support is associated with lower levels of stress resulting from the disclosure of the sexual orientation to other family members (Pollitt, Muraco, Grossman, & Russell, 2017). Family rejection is associated with lower mental health indices (Ryan, Huebner, Diaz, & Sanchez, 2009), higher indices of psychological stress and lower indices of well-being in LGB people (Shilo & Savaya, 2011).…”
mentioning
confidence: 99%